Main Characteristics of Trails on Yarmouk Forest Reserve, A Quantitative Approach to Trails Assessment - Loay Alzriqat, Sana’a Odat and Ismaiel Abuamoud (Nature Environment and Pollution Technology, 2022)
The necessity to pay attention to the tourism sector and protect natural resources has sparked a growing interest in scientific studies on the international value of ecotourism. Furthermore, eco-friendly tourist attractions should be developed and expanded to achieve long-term tourism growth. To achieve this aim, however, it is important to recognize the adverse effects of visitor activity on the natural environment and the experience of tourism to direct management activities and, thus, to maintain the resources on which ecotourism ultimately depends. This study aimed to assess the environmental impact of the four trails in the Yarmouk Forest Reserve in the Irbid governorate in northern Jordan. Field trips were used to determine the trail’s characteristics. The findings revealed a basic description of the reserve’s four routes in terms of path width, trail surface type, kind of vegetation, landscapes, and tourist attractions.